Human rights in international investment law and arbitration - Dupuy, Pierre-Marie.; Francioni, Francesco; Petersmann, Ernst-Ulrich. (Oxford : Oxford University Press, 2009)
There is a growing interplay between international investment law, arbitration and human rights. This book offers a systematic analysis of this interaction, exploring the role of principles of justice in investment law, comparing investment arbitration with other courts, and examining case studies on human rights.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Investments, Foreign (International law); Human rights; Arbitration and award